COMBINED NEPHRO- AND HEPATOPROTECTION DURING CANCER CHEMOTHERAPY: THE ROLE OF SPECIALISED AMINO ACIDS - Ergashev Nuriddin Khamzaevich; Gaziev Zoir Tohirovich (Web of Journals Publishing, 2025)
Chemotherapy of malignant neoplasms is the basis of modern oncological practice, but its effectiveness is often limited by toxic complications from the liver and kidneys. These organs play a key role in the metabolism and excretion of antitumor drugs and often become a target for cytotoxic effects. One of the promising areas of organ protection is the use of specialized amino acids with antioxidant, anti-inflammatory and metabolic protective effects.
Keywords: Chemotherapy, organ toxicity, nephroprotection, hepatoprotection, specialized amino acids, glutamine, arginine, glycine, taurine, antitumor treatment, nutritional support, hepatotoxicity, nephrotoxicity, cancer patients.